2010
DOI: 10.1063/1.3480413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface chemistry on thermal conductance at aluminum–diamond interfaces

Abstract: Articles you may be interested inEffect of van der Waals forces on thermal conductance at the interface of a single-wall carbon nanotube array and silicon AIP Advances 4, 127118 (2014); 10.1063/1.4904099 Influence of diamond surface termination on thermal boundary conductance between Al and diamondSynthetic diamond has potential as a heat spreading material in small-scale devices. Here, we report thermal conductance values at interfaces between aluminum and diamond with various surface terminations over a rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
70
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 21 publications
12
70
2
Order By: Relevance
“…This result confirms the tendency reported by Collins et al 9 , though with absolute values higher by a factor of 2. This might be owed to the use of different ways of oxidizing the surface since acid and plasma treatment was used, not heating in an oxygen-rich atmosphere 48 .…”
Section: B Effect Of Surface Treatmentssupporting
confidence: 82%
See 2 more Smart Citations
“…This result confirms the tendency reported by Collins et al 9 , though with absolute values higher by a factor of 2. This might be owed to the use of different ways of oxidizing the surface since acid and plasma treatment was used, not heating in an oxygen-rich atmosphere 48 .…”
Section: B Effect Of Surface Treatmentssupporting
confidence: 82%
“…Finally, Hopkins et al 10 recently reproduced this result with graphene instead of diamond and observed the same trends as Collins et al. In this paper, we extend the work by Collins et al 9 and we present a thorough investigation of the effect of various surface treatments on the Al/diamond TBC. The treatments that we apply to the diamond surface consist in the exposure to a plasma of pure argon, argon:hydrogen, or argon:oxygen, as well as a a mix of acids, along with the reference of an as-polished diamond.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…the TBC is mainly governed by properties of the materials on either side of the interface, but several features of the interface itself can also have a substantial influence on the resulting performance. Examples of such features include: intermixing between the layer and substrate 11 , ion bombardment of the interface 12,13 , roughness 14,15 and chemical termination of the substrate [16][17][18][19] , all of which have an impact on the TBC. Recently, Losego et al showed that there is a link between the chemical bonding at an interface between gold and quartz and the TBC of this interface by adding Self Assembled Monolayers (SAMs) between these two materials 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The effect of diamond surface characteristics on the thermal conductance of the diamond-metal interface and the thermal conductivity of the final composite materials has also been proved to be important. Oxygenated diamond samples have roughly thermal interface conductance with Al four times higher than hydrogen-treated samples [20]. Different metallic coatings have been used to effectively increase the interfacial thermal conductance [21][22][23].…”
Section: Introductionmentioning
confidence: 99%